A case report of prolonged (71 days) and continuous use of venovenous extracorporeal membrane oxygenation (VV-ECMO) without changing the line and VV-ECMO equipment in progressive respiratory failure after blunt chest injury - Balchon, Niramol; Taksaudom, Noppon; Chittawatanarat, Kaweesak; Phirompaksar, Jarin; Rimsukcharoenchai, Chartaroon; Chandacham, Kamtone; Tantraworasin, Apichat; Jirapongcharoenlap, Tidarat; Chotirosniramit, Narain (Biomedical Sciences and Clinical Medicine, 2023)
The use of extracorporeal membrane oxygenation (ECMO) in a trauma setting is a treatment preserved as a rescue therapy for unsuccessful conventional treatment modalities. A 21 year-old male patient was transferred from a secondary hospital after 2 weeks of multiple trauma, due to progressive respiratory failure, with bilateral air leakage of the lung. He received cardiopulmonary resuscitation and high setting of cardiopulmonary support. The venovenous ECMO (VV-ECMO) was initiated after fully conventional therapy failed. The clinical parameters of vital signs, gas exchange, hemodynamics and consciousness were improved after VV-ECMO was initiated. However, he could not tolerate weaning on ECMO. In addition, a massively clotted hemothorax was detected in the left lung 64 days after ECMO. The patient underwent a thoracotomy three times for blood clot removal and to stop the bleeding. Unfortunately, the patient could not tolerate the last operation and he passed away. The total time of VV-ECMO was 71 days without changing the line and equipment, and complications arose. In conclusion, this is a fi rst case in this institute of ECMO initiation in a trauma setting, with the longest duration of VV-ECMO without changing the line and equipment. However, the complications of bleeding and underlying lung pathology resulted in an adverse outcome.